Effects of dietary supplementation on vegetation cover and its defoliation by sheep in extensive husbandry - Garcia Martinez, Guillermo Carlos (2022)
Dietary supplementation is one of the most used strategies to reduce the effect of environmental fluctuations in arid and semi-arid environments. We evaluated changes in vegetation and in patterns of animal defoliation as a result of incorporating supplementation on semi-arid grasslands of Patagonia. We selected three paddocks on a sheep ranch where winter supplementation was carried out, and a feed silo was identified in each one. Fixed transects (50 m) were placed at increasing distances from the silos (100, 250 and 500 m), and several measurements were taken along the transects: grasses defoliation intensity; height, flowering and vigor of the key species; vegetation cover; and forage availability. Measurements were made during 3 seasons at two periods of the year. The defoliation intensity of species of low preference decreased with increasing distance from the silo, reaching at 100 m the same defoliation intensity as the preferred species, which did not change with distance. Vegetation, grasses and standing dead cover increased with distance from the silo. The use of dietary supplementation alters the animals’ pattern of species selection and this has consequences for plant cover. It is therefore important to consider the possible long-term effects of using this technology.